Agent-Based Simulation and Analysis of Human Behavior towards Evacuation Time Reduction - RAHMAN, ARIEF (Universiti Teknologi Petronas, 2008)
Human factors play a significant part in the time taken to evacuate following an emergency. An agent-based simulation, using the Prometheus methodology (SEEP 1.5), has been developed to study the complex behavior of human (the 'agents') in high-rise buildings evacuations. In the case of hostel evacuations, simulation results show that pre-evacuation phase takes 60.4% of Total Evacuation Time (TET). The movement phase (including queuing time) only takes 39.6% of TET. From sensitivity analysis, it can be shown that a reduction in TET by 41.2% can be achieved by improving the recognition phase. Exit signs have been used as smart agents. Expanded Ant Colony Optimization (ACO) was used to determine the feasible evacuation routes. Both the 'familiarity of environment' wayfinding method, which is the most natural method, and the ACO wayfinding, have been simulated and comparisons made. In scenario I, where there were no obstacles, both methods achieved the same TET. However, in scenario 2, where an obstacle was present, the TET for the ACO wayfinding method was 21.6% shorter than that for the 'familiarity' wayfinding method.